Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 2 - Real Numbers - 2.4 - Exponents - Problem Set 2.4: 103

Answer

$= -33$

Work Step by Step

We plug $a =-6 $ and $b = -1$ into the expression, $-a^{2} - 3b^{3}$, to obtain: $= -(-6)^{2} - 3(-1)^{3}$ $= -36 - 3(-1)$ $= -36 - (-3)$ $= -36 + 3$ $= -33$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.